Using Consumer Loss Aversion to Investigate the Effect of Stackelberg Pricing for New-Energy Vehicles - Zhang, Shuang; Du, Yueping; Wang, Linxue (Energies (Basel), 2024)
Compared to the development history of traditional FVs (fossil-fuel vehicles), although NEVs (new-energy vehicles) have many advantages and huge development potential, they are still in the early stages of development. The current research about NEV diffusion mainly focuses on policies, competition, and cooperation with FVs, as well as consumer-related factors, in which consumers are generally assumed as rational. In order to study the impact of irrational consumer factors on NEV diffusion, this study takes the prospect theory into consideration. Through a literature analysis, the loss-aversion factor is introduced to establish a Stackelberg game model, in which the FV market is the leader and the NEV market is the follower. A backward induction method is used to solve the optimal decision strategy of each party in the game, and the Python Sympy library is employed for calculation and simulation. The results show that as the loss-aversion reference point λ increases, the price, demand, and profit of NEVs increase, while the price, demand, and profit of FVs decrease, and their sum profit also shows a downward trend. While, as the loss-aversion degree k increases, the price, demand, and profit of NEVs decrease, while the price, demand, and profit of FVs increase, and their sum profit also shows an upward trend.